Asymmetric Synthesis of Adamantyl GABA Analogues - Sibiryakova, Anastasiya E.; Shiryaev, Vadim A.; Reznikov, Alexander N.; Kabanova, Anastasiya A.; Klimochkin, Yuri N. (Synthesis, 2019)
An efficient synthesis of (R)- and (S)-4-amino-3-(adamant-1-yl)butyric acids and (R)- and (S)-4-(adamant-1-yl)pyrrolidin-2-ones is presented. The synthetic strategy is based on asymmetric Michael addition of diethyl malonate to 1-(adamant-1-yl)-2-nitroethene using available Ni(II) complex as the catalyst. The procedures provide good to high enantioselectivity of Michael addition to sterically hindered nitroalkene and good yields of (R)- and (S)-enantiomers of 3-adamantyl substituted GABA.
Keywords: Michael reaction; asymmetric synthesis; metal complex catalysis; chiral GABA analogues; optical rotation calculations